Beam physics research with the IOTA electron lens. (3rd May 2021) - Stancari, G.; Agustsson, R.; Banerjee, N.; Boffo, C.; Burov, A.; Carlson, K.; Cathey, B.; Chen, Y.-C.; Chung, M.; Crawford, D.; Dhuley, R.; Eddy, N.; et al.
Abstract: The electron lens in the Fermilab Integrable Optics Test Accelerator (IOTA) will enable new research in nonlinear integrable optics, space-charge compensation, electron cooling, and the stability of intense beams. This research addresses scientific questions on high-brightness beams and operational challenges of high-power accelerators for nuclear and particle physics. We review the roles that electron lenses play in this field and the physical principles behind their applications. The design criteria and specifications for the IOTA storage ring and electron lens are then discussed. We conclude with a description of the components of the apparatus.